Oncogenic KRAS signaling activates mTORC1 through COUP‐TFII‐mediated lactate production - Byun, Jun‐Kyu (EMBO Rep, 2019)
Oncogenic signals contribute to enhanced glycolysis and mTORC1 activity, leading to rapid cell proliferation in cancer. Regulation of glycolysis and mTORC1 by PI3K/Akt signaling is well established, but how KRAS‐induced MEK signaling regulates these pathways remains poorly understood. Here, we report a role for MEK‐driven lactate production in mTORC1 activation in KRAS‐activated cells. KRAS/MEK‐induced upregulation of the chicken ovalbumin upstream promoter transcriptional factor II (COUP‐TFII) increases the expression of lactate dehydrogenase A (LDHA), resulting in lactate production and mTORC1 activation. Further, lactate inhibits the interaction of TSC2 and Rheb, leading to the cellular activation of mTORC1 irrespective of growth factor stimulation. These findings suggest that COUP‐TFII is a novel oncogenic mediator, connecting KRAS signaling and glycolysis, and leading to mTORC1 activation and cellular growth.